THE IMPORTANCE OF MEDIA LITERACY AND TEACHING METHODS IN SECONDARY SCHOOLS OF LATGALE - Kaļva-Miņina, Inga; Murinska, Sandra (Education Reform: Education Content Research and Implementation Problems, 2019)
The article analyzes how students and teachers value media literacy and its activities, and which are the most appropriate methods and study subjects for implementing media literacy in schools. Based on the results of a survey of secondary school students and teachers, the role of media literacy in education is evaluated and solutions for media literacy activities introduced in schools are provided.The results of the survey show that students and teachers seem to be interested in the topic of media literacy, and although there is enough information, there are certain topics on which they would like to talk / learn more. Respondents also emphasize the essential role of practical activities in mastering the topic of media literacy.